THE ROLE OF MANAGEMENT AND HEALTH INSURANCE IN IMPROVING THE HEALTH CARE SYSTEM - Shadmanov , A.K.; Mamatkulov , B.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The article highlights the concept of modern management, the relevance and relevance of management in the management of the healthcare system of the Republic of Uzbekistan. The main functions of management, ensuring the effectiveness of the organization's activities are given. In full growth, the question arises not so much about what the manager knows, but about how he can apply this knowledge in a changing environment to solve the problems that arise in front of him. All this and much more creates new problems that only managers who are able to change their role in organizations, apply the right decision, plan and organize work, motivate employees and control their activities can cope with. Changes in the field of health care in the conditions of doing business have a serious impact on approaches to management training. In this regard, there is a need to create a health management laboratory at TMA. Currently, state medical insurance is gradually being introduced into the health care system of the republic. For the successful implementation of this task, it is the training of personnel with a broad knowledge of health insurance, which will determine the relevance of creating a health insurance laboratory in TMA. The article describes the goals and objectives of the health insurance laboratory in optimizing the process of implementing health insurance, improving its quality and efficiency.